Communication and Listening Skills - Edward Chen (LITERA : Jurnal Bahasa Dan Sastra, 2015)
Communication is any feelings to another. Com Kresheck, and Nicolosi, with mentees. This sect listening and communic When establishing a meenvironment. This can bmentors to control the frevealed. For example, likely respond by revealthe mentee does not resmentee feel more comfomentoring relationship.